Avian Community Structure of Jhilmil Jheel Conservation Reserve, Haridwar, Uttarakhand - Das, Ankita; Krishnamurthy, Ramesh; Jayapal, Rajah (Indian Forester, 2022)
A survey of avifauna was carried out in Jhilmil Jheel Conservation Reserve (JJCR) of Haridwar Forest Division, Uttarakhand during 2018-2020. Point count method was used to count birds in six habitats viz., plantation, mixed forest, riverine habitat, scrub forest, grasslands and agriculture field. In total, 170 species of birds representing 16 orders and 64 families were recorded. The dominant order was Passeriformes, while the dominant foraging guild was insectivore birds. Most of the bird species were resident. The overall bird species diversity was 4.126. JJCR harbours 10 species of globally threatened avifauna including 3 Critically Endangered, 3 Endangered, and 4 Vulnerable species; in addition, the reserve also has 8 species of Near Threatened birds. The present documentation of avian community structure would help in developing conservation plan of this IBA.